2014
DOI: 10.1371/journal.pgen.1004344
|View full text |Cite
|
Sign up to set email alerts
|

Rad51–Rad52 Mediated Maintenance of Centromeric Chromatin in Candida albicans

Abstract: Specification of the centromere location in most eukaryotes is not solely dependent on the DNA sequence. However, the non-genetic determinants of centromere identity are not clearly defined. While multiple mechanisms, individually or in concert, may specify centromeres epigenetically, most studies in this area are focused on a universal factor, a centromere-specific histone H3 variant CENP-A, often considered as the epigenetic determinant of centromere identity. In spite of variable timing of its loading at ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 74 publications
3
55
0
Order By: Relevance
“…Recently, Rad51 and Rad52 have been implied in the deposition of the centromeric chromatin Cse4 and kinetochore assembly in C. albicans (Mitra et al, 2014). In support of this possibility, DAPI pictures from filamentous HR mutants very much resemble those of wild type (CAF2-1) cells treated with nocodazole, a drug that causes disassembly of mitotic spindles (Bai et al, 2002).…”
Section: On the Cellular And Molecular Bases Of Rad51 And Rad52 Filammentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, Rad51 and Rad52 have been implied in the deposition of the centromeric chromatin Cse4 and kinetochore assembly in C. albicans (Mitra et al, 2014). In support of this possibility, DAPI pictures from filamentous HR mutants very much resemble those of wild type (CAF2-1) cells treated with nocodazole, a drug that causes disassembly of mitotic spindles (Bai et al, 2002).…”
Section: On the Cellular And Molecular Bases Of Rad51 And Rad52 Filammentioning
confidence: 86%
“…Alternatively, differences between both yeasts in DNA damage checkpoints (Harrison et al, 2014;Loll-Krippleber et al, 2014) or in the requirements for the activation of the spindle checkpoint could account for their differential ability to filament. S. cerevisiae carries DNA sequence dependent genetically determined point centromeres, whereas formation of C. albicans centromeres, and therefore in turn kinetochore-spindle microtubule interaction is sequence independent epigenetically regulated and centromeric chromatin deposition requires Rad51 and Rad52 (Mitra et al, 2014;Sanyal et al, 2004). It is unlikely that the increase in ploidy detected in filamentous HR mutants triggers filamentation, since fluconazoletreated C. albicans cells which also showed an increase in DNA content did not filament (Harrison et al, 2014).…”
Section: On the Cellular And Molecular Bases Of Rad51 And Rad52 Filammentioning
confidence: 99%
“…In addition, some studies verified the involvement of components of the DNA damage pathway in the regulation of mitosis (35,56). Although the detailed mechanisms are not completely understood, it is evident that there exists a crosstalk between the DNA damage pathway and the regulation of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…The strains were confirmed by Southern blot analysis ( Figure S1). We previously reported that the natural rate of loss of a chromosome in wildtype C. albicans (SN148) is ,5 3 10 24 /cell/generation (Mitra et al 2014). Two independent null (sch9/sch9) mutant strains (RMKS2A and RMKS2B) exhibited a 150-to 750-fold increase in chromosome loss as compared to the spontaneous rate of loss of a chromosome ( Figure 3B).…”
mentioning
confidence: 87%
“…deletion of a centromere-proximal replication origin leads to a moderate increase in chromosome loss (Mitra et al 2014). In addition, phospho-regulation of kinetochore proteins by kinases (such as Aurora B kinase/polo-like kinase 1) has been shown to be critical for proper chromosome segregation (Shang et al 2003;McKinley and Cheeseman 2014).…”
mentioning
confidence: 99%